Fear of crime and its relationship to helping attitudes and empathy in a South African student sample - Buitendag, Juandri (My University, 2017)
Crime on campus may threaten the sustainability of society. Literature states that a university has an ethos – good or bad – and that such moral criteria can transform students’ characters, defining them for future societies. This study reviewed literature to find evidence of a relationship between empathy and helping attitudes/prosocial behaviour, as well as the psychological impact of the fear of crime and victimisation on empathy and helping attitudes. The aim was to explore the existence of a relationship between the levels of empathy in South African students at the University of the Witwatersrand, and the helping attitudes of the same student cohort. A secondary aim was to determine whether empathy and helping attitudes were influenced by the fear of crime and victimisation at a specific South African. The research design was a non-experimental, cross-sectional survey designed to assess levels of empathy, victimisation, fear of crime, and helping attitudes in students who were willing to participate in the study. A university non-probability convenience population was chosen as an appropriate source of data, in accordance with previous research conducted. Firstly, a series of analysis was run; most of the scores on the independent sample t-tests had no statistically significant effect on the scores of helping attitudes, fear of crime on campus, and empathy. The MANOVA was determined to have had no statistically significant effect on the scores of helping attitudes, fear of crime on campus and empathy. Despite the MANOVA indicating no statistically significant results, further analysis was run, the hierarchical multiple regression scores indicated a statistically significant effect on the scores of helping attitudes, fear of crime, and empathy. The significance of current research is that it looks at the progression of factors that could lead to students’ fear of crime on campus.
A research report submitted to the School of Human and Community Development, Faculty of Humanities in partial fulfilment of the requirements for the degree of Master’s in Community-Based Counselling Psychology, September 2017
Keywords: College students--Crimes against--South Africa; Universities and colleges--Security measures--South Africa; Crime--South Africa.